Mechanical power production assessment during weightlifting exercises. A systematic review - Soriano, M. A.; Kipp, K.; Lake, J. P.; Suchomel, T. J.; Marin, P. J.; Sainz De Baranda, M. P.; Comfort, P. (Sports Biomechanics, 2023)
The assessment of the mechanical power production is of great importance for researchers and practitioners. The purpose of this review was to compare the differences in ground reaction force (GRF), kinematic, and combined (bar velocity x GRF) methods to assess mechanical power production during weightlifting exercises. A search of electronic databases was conducted to identify all publications up to 31 May 2019. The peak power output (PPO) was selected as the key variable. The exercises included in this review were clean variations, which includes the hang power clean (HPC), power clean (PC) and clean. A total of 26 articles met the inclusion criteria with 53.9% using the GRF, 38.5% combined, and 30.8% the kinematic method. Articles were evaluated and descriptively analysed to enable comparison between methods. The three methods have inherent methodological differences in the data analysis and measurement systems, which suggests that these methods should not be used interchangeably to assess PPO in Watts during weightlifting exercises. In addition, this review provides evidence and rationale for the use of the GRF to assess power production applied to the system mass while the kinematic method may be more appropriate when looking to assess only the power applied to the barbell.